2015
DOI: 10.18632/oncotarget.5840
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in miR-155 regulation region contributes to lung cancer risk and survival

Abstract: Emerging evidence suggested that upregulation of miR-155 could serve as a promising marker for the diagnosis and prognosis of non-small cell lung cancer (NSCLC). In the present study, we genotyped rs767649 (A > T) located in miR-155 regulation region in 1341 cases and 1982 controls, and analyzed the associations of rs767649 with NSCLC risk and survival. Consequently, rs767649 exhibited the significant associations with the risk (adjusted OR = 1.12, 95% CI = 1.01–1.24, P = 0.031) and prognosis of NSCLC (adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 41 publications
7
43
0
3
Order By: Relevance
“…miR-155 is considered as an important oncomir and was first found within the third exon of B-cell integration cluster (BIC) gene (45) and is highly expressed in a variety of solid tumors, such as breast, lung and colon cancer (46)(47)(48). Recent research demonstrated that miR-155 was found to be induced by diverse TLR ligands through the NF-κB signaling pathways (49).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 is considered as an important oncomir and was first found within the third exon of B-cell integration cluster (BIC) gene (45) and is highly expressed in a variety of solid tumors, such as breast, lung and colon cancer (46)(47)(48). Recent research demonstrated that miR-155 was found to be induced by diverse TLR ligands through the NF-κB signaling pathways (49).…”
Section: Discussionmentioning
confidence: 99%
“…Как самостоятельный маркер miR-155 использу-ется не так часто, однако все исследователи отмечают перспективность определения данной микроРНК в ка-честве прогностического фактора при РМЖ, мелано-ме, гепатоцеллюлярной карциноме, глиомах, немелко-клеточном раке легкого (НМРЛ) и онкологических заболеваниях пищеварительного тракта [42][43][44][45][46][47][48]. Ин-тересно, что уровень продукции участников пути JAK / STAT / SOCS, контролируемых miR-155, часто используется в качестве прогностических маркеров при раке толстой и прямой кишки [49].…”
Section: солидные опухоли и Mir-155unclassified
“…Примечательно, что в нескольких работах последних лет на больших клинических выборках выявлена стати-стически значимая ассоциация функционального вари-анта miR-155 (полиморфизм rs767649) с риском развития и неблагоприятным прогнозом при НМРЛ [47], раке шейки матки [59] и гепатокарциномах [60]. Показано, что наличие в геноме вариантной аллели rs767649, обра-зующейся в результате однонуклеотидной замены (A>T) во фланкирующем интроне miR-155, может увеличивать ее транскрипционную активность.…”
Section: солидные опухоли и Mir-155unclassified
See 1 more Smart Citation
“…Finally it would be important to analyze the interaction of the SNP commented on TJP1 with the SNP rs767649 of miR-155 7 which regulates the expression of TJP1, a field not well known in the development of neurodegenerative diseases related to aging, one of the most important borders at the level epigenetic and epistasia.…”
Section: Introductionmentioning
confidence: 99%